Penggunaan High Flow Nasal Cannula sebagai Terapi Oksigen pada Kasus Covid-19 Berat dengan Obesitas: Laporan Kasus - Pratama Yulius Prabowo; Ida Bagus Gede Dwi Dharmayana; Ida Ayu Manik; I Wayan Widana; I Gede Agus Shuarsedana (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2022)
Coronavirus Disease 2019 (COVID-19) is a disease which caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). In December 2019, this disease was encountered in Wuhan, China. Covid-19 is still a global pandemic to this day. Obesity is one of the comorbidities which has been shown to increase the severity of COVID-19 cases. There is research which stated that invasive mechanical ventilation may contribute to mortality rate in severe case of COVID-19. Other than that, the increase rate of severe COVID-19 cases and the limited availability of facilities and infrastructure makes the usage of high flow nasal cannula (HFNC) begins to be considered. Aim of this case report is to represent the outcome of obese COVID-19 patient whom treated with HFNC, furthermore could evoke readers to take further research of the effectiveness of HFC usage as an oxygen therapy in severe COVID-19 cases. Case summary: 21 years old woman came to Emergency Department in Wangaya Regional Hospital with shortness of breath, unproductive cough, sore throat, and inability to smell. Patient was treated and diagnosed with confirmed severe COVID-19. She got obesity as comorbidity (weight 105 kg; height 160 cm; Body Mass Index (BMI) 41.02 kg/m2). Patient was treated for 15 days, which include 10 days of treatment in negative pressure ward in Intensive Care Unit Department (ICU). During the treatment course, patient received pharmacologic and non-pharmacologic treatment, including the administration of HFNC. After five days of HFNC usage, oxygen supplementation was downgraded to conventional oxygen supplementation (non-rebreather mask and nasal cannula). Patient then discharge without any complain and proceed self-quarantine at home. HFNC could be considered as one of non-invasive oxygen supplementation treatment in patient with severe COVID-19 disease. The initiation of usage of HFNC could be started with 30 L/minute flow, with 40% fraction of inspired oxygen (FiO2) in accordance to patient comfort with Sp02 target 92-96%. If there is an increased breathing effort, high respiratory rate, and unachieved Sp02 target, flow and inspiration fraction titrated gradually. ROX index could be used as a treatment failure indication and the need of invasive ventilation.